DNA Polymerase: Structural Homology, Conformational Dynamics, and the Effects of Carcinogenic DNA Adducts - Richard G. Federley; Louis J. Romano (Journal of Nucleic Acids)
DNA replication is vital for an organism to proliferate and lying at the heart of this process is the enzyme DNA polymerase. Most DNA polymerases have a similar three dimensional fold, akin to a human right hand, despite differences in sequence homology. This structural homology would predict a relatively unvarying mechanism for DNA synthesis yet various polymerases exhibit markedly different properties on similar substrates, indicative of each type of polymerase being prescribed to a specific role in DNA replication. Several key conformational steps, discrete states, and structural moieties have been identified that contribute to the array of properties the polymerases exhibit. The ability of carcinogenic adducts to interfere with conformational processes by directly interacting with the protein explicates the mutagenic consequences these adducts impose. Recent studies have identified novel states that have been hypothesised to test the fit of the nascent base pair, and have also shown the enzyme to possess a lively quality by continually sampling various conformations. This review focuses on the homologous structural changes that take place in various DNA polymerases, both replicative and those involved in adduct bypass, the role these changes play in selection of a correct substrate, and how the presence of bulky carcinogenic adducts affects these changes.